Tectonic Deformation of the Northeastern Tibetan Plateau and Its Surroundings Revealed With GPS Block Modeling. Issue 5 (6th May 2021) - Li, Xinnan; Pierce, Ian K. D.; Bormann, Jayne M.; Hammond, William C.; Zhang, Zhuqi; Li, Chuanyou; Zheng, Wenjun; Zhang, Peizhen
Abstract: The northeastern Tibetan Plateau and its surroundings are a tectonically complex region resulting from the continuing collision of India with Eurasia. We studied the tectonic deformation of this region using a GPS block model, which was produced using the most recently published, dense, precise, and complete GPS velocities available combined with a detailed fault geometry. The comparison between our preferred model with numerous faults and a model with fewer faults demonstrates the need for inclusion of lesser active faults affords a closer examination of strain partitioning. The predicted senses of motion and slip rates of active faults in our preferred model are consistent with the geological estimates, supporting the assumption that the decadal GPS slip rates are representative of millennial‐scale geologic slip rates. The observed fault kinematics in the northeastern Tibetan Plateau and its surroundings can be interpreted as the consequence of relative motions between different blocks and block rotations. Key Points: The inclusion of secondary active faults in block modeling affords a closer examination of strain partitioning The senses of motion and slip rates of active faults predicted by our model are generally in agreement with geologic observations Deformation of North Eastern Tibet and its surroundings can be interpreted as the result of relative motions between blocks and block rotations